Relationship between the 20-m multistage shuttle run test and 2 soccer-specific field tests for the assessment of aerobic fitness in adult semi-professional soccer players - Nassis, G. P.; Geladas, N. D.; Soldatos, Y.; Sotiropoulos, A.; Bekris, V.; Souglis, A. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to examine the relationship of 2 different field tests for the assessment of aerobic fitness in soccer players with the multistage 20-m test used for the evaluation of maximum oxygen uptake. Nineteen semi-professional male soccer players (age: 22.8 ± 2.5 mean ± SD) performed, under similar conditions, 3 field tests in a counterbalanced order 7 days apart. These tests were the multistage 20-m shuttle run test (MSRT), the Bangsbo test, and the Hoff test. Heart rate was recorded in all tests with telemetry, and the Borg scale was introduced at the end of exercise. Finally, 3-minute post-test lactate concentration was determined. Performance was 11.2 ± 0.9 levels in the MSRT, 1,658.9 ± 119.9 m in the Bangsbo test, and 1,798.2 ± 125.9 m in the Hoff test. There was a significant correlation between the Hoff test and performance in the MSRT (r = 0.49, p < 0.05). The Bangsbo test was not associated with the MSRT score (r = 0.26, p > 0.05). The maximum heart rate achieved in the Bangsbo test was significantly lower compared with that in the MSRT and Hoff test (Bangsbo: 186.6 ± 9.6, Hoff: 192 ± 7.6, MSRT: 190.4 ± 9.3 beats/min, p < 0.05). No difference was found in post-test lactate concentration among the 3 tests. In conclusion, the Hoff test can be used for the assessment of endurance in adult semi-professional soccer players. Coaches and teams could benefit from using the Hoff test that resembles soccer actions for the assessment of players' aerobic fitness.